Academic Supervision in Improving Teachers' Potential Abilities as Educators - Giantoro Giantoro; Bahrun Bahrun; Niswanto Niswanto; Giantoro Giantoro; Bahrun Bahrun (Universitas Negeri Malang, 2026)
The demands for increasing teacher professionalism place the principal's academic supervision as an important strategy in optimizing the potential abilities of teachers as educators. This study aims to analyze the implementation of academic supervision by school principals in improving the potential abilities of teachers as educators at three schools in Banda Aceh, Indonesia. The research employed a qualitative case study design. Data were collected through observation, in-depth interviews, and documentation studies involving principals and teachers as key informants. Data analysis was conducted inductively through the stages of data reduction, data presentation, and conclusion drawing. Its validity was tested through triangulation of sources and techniques. The research results show that academic supervision is implemented through three main stages: planning, implementation, and follow-up. Supervision planning is systematically developed based on an analysis of teacher needs. Supervision implementation utilizes directive, non-directive, and collaborative approaches, with the collaborative approach being the dominant approach due to its ability to build professional partnerships and reflect on learning. Supervision follow-up is carried out through individual and group coaching, internal training, and ongoing reflection, which help improve teachers' pedagogical and professional competence. This study concludes that planned, collaborative, and continuous academic supervision plays a significant role in improving teachers' potential abilities and strengthening the quality of learning in schools.